Pemanfaatan Dusun Adat Sade sebagai Laboratorium Alam dalam Praktikum Lapangan Mata Kuliah Etnosains untuk Memperkuat Kompetensi Mahasiswa Calon Guru Fisika - Hikmawati; Ni Nyoman Sri Putu Verawati; Nina Nisrina; Fathurrahman (Jurnal Pengabdian Masyarakat Sains Indonesia, 2026)
This community service activity aims to describe the utilization of Sade Traditional Village as a natural laboratory in field practicum for the Ethnoscience course to strengthen the competencies of prospective physics teachers. The activity was conducted on May 24, 2026, in Sade Traditional Village, Rembitan Village, Pujut District, Central Lombok Regency, involving 109 students from the Physics Education Study Program, Faculty of Teacher Training and Education, University of Mataram. The implementation methods included observation, interviews, documentation, cultural phenomenon analysis, and activity evaluation using questionnaires. The observed objects covered traditional weaving production, natural dyeing processes, Gendang Beleq music, Sasak traditional houses, ventilation systems of traditional houses, traditional food and medicine production, rice pounding activities, the Beladukan tradition, and traditional Sasak dances. The results showed that students gave highly positive responses to the field practicum activities. This activity enhanced learning experiences, strengthened understanding of physics and ethnoscience concepts, and supported the development of teacher candidates’ competencies in designing culture-based learning. In addition, students successfully developed ethnoscience-based learning products utilizing Sasak culture as a physics learning resource in the form of worksheets (LKPD) and posters. Thus, Sade Traditional Village has great potential as a natural laboratory that supports ethnoscience learning and strengthens the competencies of prospective physics teachers.